Propensity score matching comparison of laparoscopic versus open surgery for rectal cancer in a middle-income country: short-term outcomes and cost analysis - Tayar DO; Ribeiro Jr U; Cecconello I; Magalhães TM; Simões CM; Auler Jr JOC (Dove Medical Press, 2018)
Daiane Oliveira Tayar,1 Ulysses Ribeiro Jr,2 Ivan Cecconello,2 Tiago M Magalhães,3 Claudia M Simões,4 José Otávio C Auler Jr1 1Department of Anesthesia and Critical Care, University of São Paulo, Faculty of Medicine, São Paulo, Brazil; 2Department of Gastroenterology, University of São Paulo, Faculty of Medicine, São Paulo, Brazil; 3Department of Statistics, Institute of Exact Sciences, Federal University of Juiz de Fora, Juiz de Fora, Brazil; 4Department of Anesthesia and Critical Care, Cancer Institute of the State of São Paulo, São Paulo, Brazil Background: Laparoscopic surgery for rectal cancer is associated with improved postoperative outcomes compared to open surgery; however, economic studies have yielded contradictory results. The aim of this study was to compare the clinical and economic outcomes of laparoscopic versus open surgery for patients with rectal cancer.Methods: Propensity score matching analysis was performed in a retrospective cohort of patients who underwent elective low anterior resection for rectal cancer treatment by laparoscopic and open surgery in a single Brazilian cancer center. Matched covariates included age, gender, body mass index, pTNM stage, American Society of Anesthesiologists score, type of anesthesia, neoadjuvant chemoradiotherapy, and interval between neoadjuvant chemoradiotherapy and index surgery. The clinical and economic outcomes were evaluated. The follow-up period was within 30 days of the index procedure. The clinical outcomes were reoperation, postoperative complications, operative time, length of stay in the intensive care unit, and postoperative hospital stay. For economic outcomes, a cost analysis was used to compare the costs.Results: Initially, 220 patients were evaluated. After propensity score matching, 100 patients were included in the analysis (50 patients in the open surgery group and 50 patients in the laparoscopic surgery group). There were no differences in patients’ baseline characteristics. Operative time was longer for laparoscopic surgery (247 minutes vs 285 minutes, P=0.006). There were no significant differences in other clinical outcomes. The hospital costs were similar between the two groups (Brazilian reais 21,233.15 vs Brazilian reais 21,529.28, P=0.115), although the intraoperative costs were higher for laparoscopic surgery, mainly owing to the surgical devices and the theater-related costs. The postoperative costs were lower for laparoscopic surgery, owing to lower intensive care unit, ward, and reoperation costs.Conclusion: Laparoscopic surgery for rectal cancer is not costlier than open surgery from the health care provider’s perspective, since the intraoperative costs were offset by lower postoperative costs. Open surgery tends to have a longer length of stay. Keywords: rectal cancer, laparoscopy, open surgery, propensity score matching, health care costs, cost analysis